Pengaruh Terpaan Tayangan Religi di Televisi Terhadap Sikap dan Perilaku Taqwa Pemirsa - Chendi Liana; Herta Armianti; Muhammad Ali (Jurnal Dakwah dan Komunikasi, 2017)
This research entitled Influence of Impression on Religious Display on Television (Trans TV) on attitude and behavior of Taqwa Pemirsa (Student of Attahiriah Islamic University), which aims to 1) to know about exposure of religious event in Trans TV to viewers, ie Attahiriah University students, 2) Attitudes and behaviors of the audience, and 3) knowing whether the religious event's exposure to the audiences affected their attitude and piety behaviors. Research using correlation method using sampling technique, purposive sampling. Which with the formula Yamane obtained 98 respondents from the University Attahiriyah. Data collection tools used are questionnaires, observation and literature study. This research uses S-O-R model (stimulus-organism-response) and AIDDA (Attention, Interest, Desire, Decision, Action). Model S-O-R to see the effect of stimuli in the form of religious impressions to the audience (organisms) in which the response is the attitude and behavior of taqwa. While the AIDDA Model to see whether the attention of the attention will generate interest, then desire, then influence the decision and action as conveyed in the message in the show, such as attitude and Taqwa behavior. Research shows the relationship between variables X and variable Y is a high correlation between religious impressions Impression on attitudes and behavior of university students attitudes taqwa. After calculation using correlation Pearson's correlation formula (product moment) obtained correlation coefficient value of 0.79. So that the influence of exposure to religious impressions is important to create or foster attitudes and behavior of the audience, especially students attahiriyah.